2017
DOI: 10.1111/apt.14377
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical study: the effects of oral taurine 6g/day vs placebo on portal hypertension

Abstract: Taurine is safe and may reduce portal pressure in cirrhotic patients. More studies on the underlying mechanisms of action and long-term effects of taurine supplementation are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The Vienna Hepatic Hemodynamic Laboratory at the Medical University of Vienna performed the HVPG measurements according to a standardised operating procedure . HVPG measurements were performed in the absence of nonselective beta blockers and nitrates.…”
Section: Methodsmentioning
confidence: 99%
“…The Vienna Hepatic Hemodynamic Laboratory at the Medical University of Vienna performed the HVPG measurements according to a standardised operating procedure . HVPG measurements were performed in the absence of nonselective beta blockers and nitrates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is possible that certain populations have been underrepresented across the available meta-analysed studies. The studies were conducted in Europe [28][29]31], Asia [27,30] and the Middle East [25][26], yet there were no studies conducted in larger continents, such as the North and South America, Africa or Australasia, where similar risks of mortality due to cardiovascular disease are present and increased in certain ethnic groups [55]. This could be partly addressed with changes in dietary supplementation, including changes in taurine intake.…”
Section: Discussionmentioning
confidence: 99%
“…1 The data suggested that taurine may be a useful interventional tool for replacing non-selective beta blockers (NSBBs) when use of NSBBs is contraindicated. Another important aspect of this work was measurement of steady state serum taurine concentration; day 28 serum level of taurine (7.79 ng/lL) was 10-fold higher than placebo group (0.73 ng/lL) 1 As a clinical pharmacologist, I had a few questions: on dose selection, influence of the dose on absorption, distribution and excretion of taurine which would be critical for efficacy; likelihood of interference in the absorption of co-medications. A quick introspection/rationalisation to these may be beneficial for the design of future studies of taurine.…”
Section: Editorsmentioning
confidence: 99%